1991
DOI: 10.1159/000186480
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tubular Protein Handling in Experimental Renal Disease

Abstract: Competitive inhibition of renal tubular transport occurs between low- and high-molecular-weight proteins following intravenous infusion, but this relationship is less clear following de novo glomerular or renal tubular injury. The present study evaluated renal lysozyme and albumin handling following renal tubular injury induced by both low- and high-dose mercuric chloride (0.5 and 2.0 mg/kg) and maleic acid (50 and 400 mg/kg), and following glomerular injury induced by puromycin aminonucleoside (5 mg/100 g) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
2
5
2
Order By: Relevance
“…Our observations on PAN-or Adriamycin-treated rats are, thus, at variance with those of Houser and Milner [11] who failed to evidence an inhibition of lysozyme reabsorp tion in these models. This failure is presumably due to the fact that, although the same dosage as in our study was used, values of albuminuria did not exceed 200 mg/24 h and were, thus, in most cases, below the threshold estimated in figure 3.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Our observations on PAN-or Adriamycin-treated rats are, thus, at variance with those of Houser and Milner [11] who failed to evidence an inhibition of lysozyme reabsorp tion in these models. This failure is presumably due to the fact that, although the same dosage as in our study was used, values of albuminuria did not exceed 200 mg/24 h and were, thus, in most cases, below the threshold estimated in figure 3.…”
Section: Discussioncontrasting
confidence: 55%
“…This theory as sumes that low-and high-molecular-weight (Mr) proteins are reabsorbed by different mechanisms and that cationic and anionic proteins can not compete with each other because of constraints in the access to endocytotic sites. The second theory, formulated initially by Hardwicke and Squire [4] in the 1960s, postulates that the tubular transport of proteins is an unselective process involving common endocytotic sites for which proteins present different af finities according to their molecular characteristics [5,6], This theory relies mainly on the finding that proteins, what-ever their size and charge, can compete with each other for uptake by the rat kidney [5][6][7][8], In particular, high-Mr pro teins such as albumin were found to inhibit the uptake of small-size proteins like |)2-microglobulin (|V m) or lysozyme [5,6], Although this theory has received further support from in vitro and in vivo studies [9,10], it has been recently questioned by the investigations of Houser and Milner [11] on the renal handling of albumin and lysozyme in ex perimental diseases involving primarily the glomerulus (puromycin aminonucleoside, PAN, and Adriamycin) or the tubule (mercuric chloride and maleic acid). These authors found that the massive albuminuria induced by PAN or Adriamycin was not associated with an increased lysozymuria.…”
Section: Introductionmentioning
confidence: 99%
“…and a 40-fold rise in excre tion of the freely filtered but normally reabsorbed lowmolecular-weight protein lysozyme. There was a smaller increase in albuminuria (which is also consistent with mild tubular injury [17]) and only a modest rise in IgG excretion. Further evidence of tubular abnormalities was obtained from immunohistochemical staining with anti bodies against Tamm-Horsfall protein, using a technique described by Howie et al [ 18].…”
Section: Discussionsupporting
confidence: 64%
“…[1][2][3][4][5] This is determined by measuring urinary protein, usually albumin in the urine by radioimmunoassay (RIA) or by nonspecific total protein assays involving precipitation or by dye-binding protein assays. To account for these increases, a model of large pores, has been proposed 6,7 because it had been assumed that virtually all proteins filtered by the kidney are excreted intact.…”
mentioning
confidence: 99%
“…Puromycin aminonucleoside (PAN) 1,3,10,[17][18][19][20] and anti-GBM antibodies 2,4,21,22 have both been used to induce massive glomerular injury. Pronounced morphological changes at the GCW are induced by PAN including a loss of foot process, a spreading of epithelial cell cytoplasm, a lifting of focal areas of the epithelial cells, 18 the appearance of microvilli, 3 and a thin, less compact appearance to the GBM.…”
mentioning
confidence: 99%